Celebrating Homosexuality and Female Masculinity in Kimberly Peirce’s movie Boys Don’t Cry - Pandey, Ashok Raj (Rural Development Journal, 2017)
This research argues that Kimberly Peirce’s movie “Boys Don’t Cry” can be read as emancipative gender narrative that strongly resists Heteronormativity and hegemonic masculinity by putting forward female masculinity and celebrating homosexual identity. Our paper focus on some ways narrative has deliberately challenged gender discourse; firstly by resisting Heteronormative social complex and secondly by dismantling male-centric masculinity. This paper further claims that the expression of each rebellious dialogue and contexts within the narrative of Boys Don’t Cry have contributed to give alternative justice for all socially victimized transgender. It also explains the way movie questions the long sustained subjectivities of heterosexual gender discourse and tries to normalize the existence of LGBT (lesbian, gay, bisexual, and transgender) population in American society. Our paper develops to the conclusion that the 1999 crime drama Boys Don’t Cry not only advocates gender freedom but also exposes homosexual realities and the brutal consequence of society’s failure to accept this fact.